Advantages and challenges of the gig economy: perspective from potential hospitality employees - Tay, Kei Win; Mohamad, Siti Fatimah (UiTM Press, 2022)
The gig economy has currently emerged as a trending type of workforce. However, there is not much research found within the Malaysian hospitality industry. This study aimed to explore the gig economy’s advantages and challenges using a qualitative approach. Interviews were conducted with hospitality final-year students from Malaysian public universities. Ten students from five different universities participated in this study, and the data were analyzed using thematic analysis. The results discovered three advantages of the gig economy from the participants' perspectives: flexibility, high pay, and low stress. Meanwhile, there were six challenges of the gig economy: absence of benefit, unpredictable, high competition, self-work equipment, personal development, and work environment. The results are anticipated to shed light on improving the gig economy in the Malaysian hospitality industry, particularly from related stakeholders such as policymakers, industry and higher education institutions.